Transmission System Operation Challenges with Large Wind Penetration - Kincic, Slaven; Zhang, Hongming (Journal of Technology Innovations in Renewable Energy, 2014)
The State of California’s renewable energy policies and energy incentives are the main drivers of renewable generation development occurring in the Pacific Northwest. The largest wind integration efforts are happening within the Bonneville Power Administration’s (BPA) Balancing Area (BA). BPA is approaching a 40 percent wind penetration factor. Such a large wind penetration imposes significant challenges on the transmission system operation requiring more system studies in operational time frame. These challenges include needs for additional voltage regulation requiring more switching operations, dealing with higher ramping rates and carrying additional regulation reserve as well as additional difficulty in Columbia River management (river scheduling). This paper discus some of those challenges in more details.